2014
DOI: 10.1002/humu.22548
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel 5′ AlternativeCFTRmRNA Isoform in a Patient with Nasal Polyposis andCFTRMutations

Abstract: Cystic fibrosis may be revealed by nasal polyposis (NP) starting early in life. We performed cystic fibrosis transmembrane conductance regulator (CFTR) DNA and mRNA analyses in the family of a 12‐year‐old boy presenting with NP and a normal sweat test. Routine DNA analysis only showed the heterozygous c.2551C>T (p.Arg851*) mutation in the child and the father. mRNA analysis showed partial exon skipping due to c.2551C>T and a significant increase in total CFTR mRNA in the patient and the mother, which was attri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Young's syndrome, also named sinusitis-infertility syndrome, is a rare and inherited syndrome characterized by chronic sinusitis, bronchiectasis, and decreased fertility due to azoospermia. Various studies have suggested that mutation in the Cftr gene may be involved in the pathogenesis of CRS as well as Young's syndrome 39 42 . Furthermore, a previous study suggested that the up-regulation of a member of matrix metalloproteinase, namely disintegrin and metalloproteinase (ADAM)-33 protein, is associated with the pathogenesis of nasal polyps 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Young's syndrome, also named sinusitis-infertility syndrome, is a rare and inherited syndrome characterized by chronic sinusitis, bronchiectasis, and decreased fertility due to azoospermia. Various studies have suggested that mutation in the Cftr gene may be involved in the pathogenesis of CRS as well as Young's syndrome 39 42 . Furthermore, a previous study suggested that the up-regulation of a member of matrix metalloproteinase, namely disintegrin and metalloproteinase (ADAM)-33 protein, is associated with the pathogenesis of nasal polyps 43 .…”
Section: Discussionmentioning
confidence: 99%